[Objects relating to prominent Australians and Australian events : ephemera material collected by the National Library of Australia]
The ephemera collection contains documents of everyday life generally covering publications of fewer than five pages. These may include: advertising material, area guides, booklets, brochures, samples of merchandise postcards, posters, programs, stickers and tickets.
Kevin Rudd coffee mug -- Julia Gillard coffee mug -- Gough Whitlam "It's time" coffee mug -- Bob Hawke lager can -- Admission pass to world premiere of 'Ned Kelly'.
A collection of objects (or realia) produced to made to commemorate a prominent Australian person, mark a siginificant Australian event, etc.
National Library of Australia's 'Hawke's Lager' beer can and coaster exhibited: “Treasures Gallery”, National Library of Australia, 20a May to November 2020.
Keywords: Gillard, Julia -- Realia; Rudd, Kevin, -- 1957- -- Realia; Ledger, Heath, -- 1979-2008 -- Realia; Politicians -- Australia -- Realia; Celebrities -- Australia -- Realia; Prime ministers -- Australia -- Realia; Printed ephemera -- Australia; Australian